Safe administration of chemotherapy in mast cell activation syndrome. (June 2021) - Lythgoe, MP; Krell, J; McNeish, IA; Tookman, L
Introduction: Mast Cell Activation Syndrome (MCAS) is an immunogenic disorder typically presenting with episodic multi-organ symptoms, caused by the inappropriate and aberrant release of mast cell mediators. Symptoms may be severe, including anaphylaxis and often occur in response to specific triggers which include many drugs and potentially chemotherapeutic agents. The administration of adjuvant chemotherapy and radiotherapy in endometrial cancer significantly reduces the risk of reoccurrence in patients with high risk disease. Currently there is no evidence or case reports to guide the safe administration of chemotherapy in MCAS patients. Case report: We present the case of a 59-year-old lady with stage 3 A grade 2 endometroid endometrial cancer who underwent successful surgical management. She then received 4 cycles of adjuvant chemotherapy in the form of carboplatin and paclitaxel. This case describes a staged approach to chemotherapy administration and the utilisation of a carboplatin desensitization regimen to reduce the risk of immediate and delayed hypersensitivity sequalae. Management & outcome: Utilising an enhanced pre-medication strategy and a staged approach to chemotherapy administration, she was able to complete adjuvant treatment without any serious complications. At the date of censoring (May 2020) she has not shown any evidence of disease re-occurrence. Discussion & conclusion: Administering chemotherapy to patients with any mast cell disorder remains challenging. We hope that this case may provide the framework for safer chemotherapy administration for any patients at high risk of serious hypersensitivity sequalae in endometrial cancer and beyond.